Pengembangan Smart Motor untuk Pencegahan Tindak Kriminal Pencurian Kendaraan Roda 2 - Herpendi Herpendi; H.S. Utomo; V. Julianto (Universitas PGRI Semarang, 2020)
Every year the production motorcycles has increased. In 2017 to 2018 the increase reached 8,112,364 units or 7.24%. Motorcycles are the most popular among Indonesian people, especially the lower middle class to facilitate mobilization in daily activities. As the rapid growth of motorcycle, the number of criminal motorcycles theft is also high. criminal motorcycles data for 2018 amounted to 27,731 cases and for 2017 there were 35,226 cases. Motorcycles are often the object of theft because it is easier in terms of mobilization in terms of the theft process to the sale to collectors compared cars and above. In addition, the security side provided by motorcycles manufacturers is still relatively low, only a few manufacturers have listed an alarm feature in their production. The modus operandi that the perpetrators often use is to destroy the key house by using the T key, but also by seizing directly, pretending to borrow to spread nails on certain streets. This study aims to develop a tool (Smart motor) that can be used as an anti-theft security with the media validation of the driver's license and vehicle registration so that the motor can not be turned on if it does not bring the driver’s licence and vehicle registration registered on the device. With the device built, the owner is required to bring the vehicle registration and driver’s licence so that the motor can be turned on. This is also useful in order to comply with traffic rules set by the police, namely by carrying a complete driving while traveling